Splash of body fluids among healthcare support staff in Ghana: a cross-sectional study - Philip Apraku Tawiah; Emmanuel Appiah-Brempong; Paul Okyere; Mary Eyram Ashinyo (SAGE Open Medicine, 2024)
Background: Exposure to splash of body fluids is one of the common ways of transmitting blood-borne infections from patients to healthcare practitioners. Globally, there is a paucity of evidence on exposure to splash of body fluids among hospital housekeepers. This study, therefore, investigated splash of body fluid and its predisposing factors among healthcare support staff in the Greater Accra region, Ghana. Methods: An analytic cross-sectional survey was conducted among support staff in 10 major hospitals between 30 January and 31 May 2023. A multi-stage sampling procedure was the overarching technique employed, and study participants were recruited through simple random and probability proportional-to-size sampling techniques. The data analyses were conducted using STATA 15 software. The preliminary association between exposure to splash of body fluids and predisposing factors was established through Chi-square, Fisher’s exact, and Mann–Whitney U tests. Log-binomial regression analyses were employed to validate the factors related to splash of body fluids at a significance level of p -value < 0.05. Results: The investigation was conducted among 149 healthcare support staff. The exposure to splash of body fluids over the past 1 year was 53.7% (95% CI: 45.3%–61.9%). The types of body fluids that were mostly encountered through these splash exposures were amniotic fluids (36.3%) and urine (23.8%). Several factors were found to be significantly associated with splash of body fluids, namely: employed as a healthcare assistant [APR = 1.61 (1.16, 2.22)], holding a supervisory position [APR = 0.24 (0.11, 0.51)], having a system in place for reporting body fluid splashes [APR = 0.61 (0.44, 0.85)], male healthcare support staff [APR = 0.62 (0.41, 0.93)], and adherence to standard precautions most of the time [APR = 1.66 (1.11, 2.48)]. Conclusion: Healthcare support staff were highly exposed to splash of body fluids. Gender, supervisory role, category of worker, reporting systems, and adherence to standard precautions were associated with exposure to splash of body fluids. Facility managers are advised to enhance the efficiency of reporting systems.